The Throne of Fire : The Kane Chronicles #2 - Riordan, Rick (New York : Disney/Hyperion Books, 2011)
Carter and Sadie, offspring of the brilliant Egyptologist Dr. Julius Kane, embark on a worldwide search for the Book of Ra, but the House of Life and the gods of chaos are determined to stop them.
Keywords: Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Mythology, Egyptian -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Voyages and travels -- Fiction; Egyptian mythology -- Fiction; Magic -- Fiction; Siblings -- Fiction; Adventure fiction